Corporate Governance Mechanisms, Capital Intensity, and Tax Avoidance: An Empirical Study of Banking Transparency - Yovita Kristanti Magiyono; Erna Lovita (Research of Accounting and Governance, 2026)
This study examines the effects of independent boards of commissioners, boards of directors, audit committees, institutional ownership, and capital intensity on tax avoidance in Indonesian banking companies during 2020–2024. The study is motivated by concerns over persistent tax avoidance despite corporate governance regulations. The banking sector was selected because of its strategic role in economic stability and strict regulatory environment, making governance transparency particularly important. This research also addresses inconsistent findings regarding the effectiveness of corporate governance mechanisms in reducing tax avoidance. A quantitative associative approach was employed using secondary data from banking companies listed on the Indonesia Stock Exchange (IDX). Purposive sampling yielded 20 companies, resulting in 100 firm-year observations. Panel-data regression analysis was conducted using EViews. The results indicate that independent boards of commissioners, institutional ownership, and capital intensity have significant negative effects on tax avoidance, suggesting that stronger independent oversight, greater institutional investor participation, and higher fixed-asset intensity discourage aggressive tax practices. In contrast, the board of directors and audit committee have no significant effect. These findings contribute to the corporate governance and agency theory literature by highlighting the importance of governance quality in reducing tax avoidance and promoting greater tax transparency in Indonesia's banking sector.